Linking drought-resistance mechanisms to drought avoidance in upland rice using a QTL approach progress and new opportunities to integrate stomatal and mesophyll responses - Price, Adam H (Journal of experimental botany, 2002)
The advent of saturated molecular maps promised rapid progress towards the improvement of crops for genetically complex traits like drought resistance via analysis of quantitative trait loci (QTL). Progress with the identification of QTLs for drought resistance-related traits in rice is summarized here with the emphasis on a mapping population of a cross between drought-resistant varieties Azucena and Bala. Data which have used root morphological traits and indicators of drought avoidance in field-grown plants are reviewed, highlighting problems and uncertainties with the QTL approach. The contribution of root-growth QTLs to drought avoidance appears small in the experiments so far conducted, and the limitations of screening methodologies and the involvement of shoot-related mechanisms of drought resistance are studied. When compared to Azucena, Bala has been observed to have highly sensitive stomata, does not roll its leaves readily, has a greater ability to adjust osmotically, slows growth more rapidly when droughted and has a lower water-use efficiency. It is also a semi-dwarf variety and hence has a different canopy structure. There is a need to clarify the contribution of the shoot to drought resistance from the level of the biochemistry of photosynthesis through stomatal behaviour and leaf anatomy to canopy architecture. Recent advances in studying the physical and biochemical processes related to water use and drought stress offer the opportunity to advance a more holistic understanding of drought resistance. These include the potential use of infrared thermal imaging to study energy balance, integrated and online stable isotope analysis to dissect processes involved in carbon dioxide fixation and water evaporation, and leaf fluorescence to monitor photosynthesis and photochemical quenching. Justification and a strategy for this integrated approach is described, which has relevance to the study of drought resistance in most crops